2022
DOI: 10.1002/ird.2698
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gravity‐led and energy‐fed drainage for sustaining food security in the polders of the coastal zone of Bangladesh

Abstract: Bangladesh is currently self‐sufficient in rice production but faces immense challenges of sustaining that self‐sufficiency because of population growth and climate change. There is little scope to further increase cropping intensity except in the underutilized 1.2 Mha of lands enclosed in the polders of the coastal zone. The main impediment to wide‐scale adoption of more productive cropping systems in the polders is poor drainage that often results in waterlogging. Therefore, a study was conducted in polder 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Many rural households in the polder zones are highly vulnerable and struggle to meet their food needs in this climate-affected environment (Kabir et al, 2020). Shifting to HYVs of rice, coupled with improved drainage facilitated by strategic sluice gate operations, boosted aman season productivity by a minimum of 1.5 tonnes per hectare compared to traditional farming practices (Mondal et al, 2022). These findings hold profound implications for the food security of farming households residing in the 1.2-million-hectare polder zone.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Many rural households in the polder zones are highly vulnerable and struggle to meet their food needs in this climate-affected environment (Kabir et al, 2020). Shifting to HYVs of rice, coupled with improved drainage facilitated by strategic sluice gate operations, boosted aman season productivity by a minimum of 1.5 tonnes per hectare compared to traditional farming practices (Mondal et al, 2022). These findings hold profound implications for the food security of farming households residing in the 1.2-million-hectare polder zone.…”
Section: Discussionmentioning
confidence: 89%
“…The issue of waterlogging poses a significant challenge in the polder zone, causing extensive damage to agriculture (Alam et al, 2017). Mondal et al (2022) demonstrated the potential for reducing waterlogging in polder 30 through gravity drainage, given that the elevation of most agricultural land is higher than river water levels during low tides. Effective water management practices, particularly drainage, are critical for enhancing production and addressing food insecurity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations